1989
DOI: 10.2337/diacare.12.6.435
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Low-Protein Diets: Where's the Beef?

Abstract: The earliest signs of renal impairment in the diabetic patient traditionally marked the onset of an era of frustration for both physician and patient. Aside from meticulous control of hypertension, there was little to do to alter the inexorable course to dialysis or transplantation. However, if the recent reports touting the benefits of low-protein diets are correct, all of this may soon change; these diets may delay or prevent end-stage renal insufficiency. The question is whether these diets are safe as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1990
1990
2002
2002

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…5 The latent heat accompanying the transition has also been observed at a Hg/aqueous electrolyte interface. 28,29 The above E values fall well into the range where Chu et al 5 observed the transitions at the RuO 2 electrode by synchrotron radiation X-ray scattering methods. Also, these values fall very close to the field acting on the water molecules lying at the maximum of RDF in the first hydration shell of the Sr 2+ ion, which enabled us to provide a tentative explanation of its peculiar properties revealed by neutron scattering.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…5 The latent heat accompanying the transition has also been observed at a Hg/aqueous electrolyte interface. 28,29 The above E values fall well into the range where Chu et al 5 observed the transitions at the RuO 2 electrode by synchrotron radiation X-ray scattering methods. Also, these values fall very close to the field acting on the water molecules lying at the maximum of RDF in the first hydration shell of the Sr 2+ ion, which enabled us to provide a tentative explanation of its peculiar properties revealed by neutron scattering.…”
Section: Discussionsupporting
confidence: 58%
“…Yet another study concerned the mercury/aqueous electrolyte interface. By laser temperature jump method at 293 K thermal phenomena have been observed 28,29 which were interpreted by the Authors as accompanying a phase transition. In a field of strength 10 9 V m À1 changes in entropy S have been found of the same order of magnitude as that seen in our Fig.…”
Section: Thermal Effect At the Transitionmentioning
confidence: 91%
“…Lattice models have been used in molecular modeling of adsorption. We have shown in several papers, that the Ising lattice gas model is a valid model for 2D first-order phase transitions, contrary to the Frumkin model. The Ising lattice gas model considers the existence of 2D gas clusters and 2D liquid clusters (the Frumkin model only monomers) and the corresponding possible configurations.…”
Section: Introductionmentioning
confidence: 99%